Pemberdayaan Petani Melaluirejuvenasi Kelompok dan Pengolahan Limbah Sawit-Sapi di Kampung Sialang Palas-Siak - Khairul Anwar; Adiwirman Adiwirman; Dahlan Tampubolon; Ali Yusri (Unri Conference Series: Community Engagement, 2021)
Lubuk Dalam District is one of the sub-districts in Siak Regency which has the largest oil palm plantation area. In this area there are 12 farmer groups (Poktan) with 610 members. One of the best oil palm Poktans is Karya Bersama located in Sialang Palas Village. This Poktan has a legal entity No. AHU-0048970. AH. 01. 07 and consists of 32 farmers. Today Poktan faces a big problem related to productivity during the Covid-19 period. Previously, Karya Bersama farmers were a productive society. However, since the pandemic, the productivity of this group tends to decrease drastically, although the desire to continue to excel is still high. The question is, how to increase the productivity of the Karya Bersama Poktan through rejuvenation in Sialang Palas Village? In finding a solution to this problem, this service activity collaborates with PPL, students of Kukerta Unri 2021, offering systematic solutions for structuring group relations and technology to farmers in cultivating potential. The methods are FGD, socialization, webinars, implementing the Sawit-Ku application, training on palm and livestock waste management, and mentoring with PPL and village government officials. Second, TTG in processing palm oil and livestock waste in the form of plates, mats, briquettes and fertilizers. In the long term, this empowerment activity is expected to be a productivity lever for self-help Poktan, especially during the pandemic.